Comparison of endogenous amino acid losses in broilers when offered nitrogen-free diets with differing ratios of dextrose to corn starch - Zhou, Huajin; Wu, Wei; Mahmood, Tahir; Chen, Yanhong; Xu, Yanwei; Wang, Youli; Yuan, Jianmin (Scientific reports, 2022)
The nitrogen-free diet (NFD) method is widely used to determine the ileal endogenous amino acids (IEAAs) losses in broiler chickens. Starch and dextrose are the main components of NFD, but the effects of their proportion in the NFD on the IEAAs and the digestive physiology of broilers are still unclear. This preliminary study aims to explore the best proportion of glucose and corn starch in NFD to simulate the normal intestinal physiology of broilers, which helps to improve the accuracy of IEAAs determination. For this purpose, 28-day-old broiler chickens were allocated to five treatment groups for a 3-day trial, including a control group and four NFD groups. The ratios of dextrose to corn starch (D/CS) in the four NFD were 1.00, 0.60, 0.33, and 0.14, respectively. Results noted that NFD significantly reduced serum IGF-1, albumin, and uric acid levels compared with the control ( P < 0.05), except there was no difference between group D/CS 0.33 and the control for IGF-1. The increased Asp, Thr, Ser, Glu, Gly, Ala, Val, Ile, Leu, His, Tyr, Arg, and Pro contents of IEAAs were detected in broilers fed the NFD with a higher ratio of D/CS (1.00 and 0.60) compared to the lower ratio of D/CS (0.33 and 0.14). Moreover, ileal digestibility of dry matter and activity of digestive enzymes increased as the D/CS elevated ( P < 0.001). Further investigation revealed that the number of ileal goblet cells and Mucin-2 expression were higher in the group with D/CS at 1.00 when compared with group D/CS 0.33 and the control ( P < 0.05). Microbiota analysis showed that NFD reshaped the gut microbiota, characterized by decreased microbial diversity and lower abundance of Bacteroidetes , and increased Proteobacteria ( P < 0.05). Our results indicate that a higher D/CS ratio (1.00 and 0.60) in NFD increases IEAAs by promoting digestive enzymes and mucin secretion. However, the excessive proportion of starch (D/CS = 0.14) in NFD was unsuitable for the chicken to digest. The chickens fed with NFD with the D/CS ratio at 0.33 were closer to the normal digestive physiological state. Thus, the ratio of D/CS in NFD at 0.33 is more appropriate to detect IEAAs of broiler chickens.